Cost Estimates of Producing Pink Guava in South Florida - Edward A. Evans; Fredy H. Ballen; Jonathan H. Crane; Aditya Singh (EDIS)
This publication presents the estimated costs and returns associated with the operation of an established pink guava grove in south Florida. The information presented was collected through field interviews with growers and industry specialists; it reflects a wide diversity of production techniques in small guava orchards. The information presented is intended only as a reference to estimate the financial requirements of operating an established pink guava grove.